Jolly roger and the pirates of captain abdul - McNaughton, Colin (Walker Books London, 2005)
Nine-year-old Roger is a miserable landlubber with a bad-tempered mother. When he is bagged by pirates to be a cabin boy, he finds himself aboard the Golden Behind with the smelliest, hairiest, scariest pirates the world has ever seen. Originally published: 1988